Modified Sanjia Powder ameliorates cognitive impairment and exerts neuroprotective effects in 5 × FAD mice: insights from quantitative proteomics - Wang, Yifan; Liu, Chenxi; Zheng, Xiaoyan; Wang, Zhiqiang; Wang, Yufan; Geng, Yi; Yang, Jin; Wei, Kaifeng; Chen, Xiaoying (Frontiers in Nutrition, 2026)
BackgroundModified Sanjia Powder (MSP) is a traditional Chinese herbal formulation with potential use as a dietary supplement, which has shown neuroprotective properties against Alzheimer's disease (AD). However, its mechanisms of action, particularly those related to metabolic pathways, remain poorly understood. Given the emerging role of lipid metabolism and associated oxidative stress in AD pathogenesis, this study aimed to investigate the therapeutic effects of MSP on cognitive impairment and explore its molecular mechanisms, with emphasis on nutritionally relevant pathways, in the 5 × FAD mouse model of AD using quantitative proteomics.MethodsCognitive, pathological, and molecular functions were evaluated following MSP treatment. Cognitive performance was assessed using behavioral tests including the Y-maze, novel object recognition (NOR), and Morris Water Maze. Brain tissues from control, 5 × FAD, and MSP-treated mice were analyzed by data-independent acquisition mass spectrometry to identify differentially expressed proteins (DEPs). Key findings were validated using Western blotting, immunohistochemistry, and cytokine assays.ResultsMSP treatment significantly improved cognitive function in 5 × FAD mice across multiple behavioral tests. It reduced Aβ plaque deposition, attenuated tau hyperphosphorylation, inhibited microglial activation, and decreased levels of pro-inflammatory cytokines (IL-1β, TNF-α, and IL-6). Proteomic analysis identified 460 DEPs, with significant enrichment in pathways related to fatty acid biosynthesis, lipid metabolism, and oxidative stress. Notably, among these DEPs, ACSL4—a key regulator of lipid metabolism and oxidative stress—was upregulated in 5 × FAD mice but markedly downregulated after MSP treatment. Importantly, MSP's modulation of lipid metabolism appeared selective for the ACSL4 pathway, without broadly affecting other lipid metabolic pathways that influence cytokine release. MSP also reduced levels of reactive oxygen species (ROS) and lipid peroxidation markers (MDA and 4-HNE).ConclusionMSP confers neuroprotection in AD by modulating ACSL4-mediated lipid metabolism and oxidative stress, leading to improved cognitive function and reduced neuroinflammation in the 5 × FAD mouse model. These results position MSP as a promising therapeutic candidate for AD and demonstrate the value of quantitative proteomics in elucidating the mechanisms of traditional Chinese medicines.